Public perceptions of the role of government and nonstate actors in responding to COVID‐19. Issue 3 (8th March 2021) - Sledge, Daniel; Thomas, Herschel F.
Abstract: In this article, we examine public perceptions of the importance of different levels of government and of nongovernmental entities in responding to the COVID‐19 pandemic. By analyzing the case of COVID‐19, we illuminate patterns that may be helpful for understanding public perceptions of the response to a broader range of crises, including the impacts of hurricanes, tornadoes, earthquakes, wildfires, and other hazards. We contribute to the public policy literature on public perceptions of government response to crises and expand it to include consideration of the role of nonstate actors. Drawing on a representative survey of 1200 registered voters in Texas, we find that individuals are more likely to view government as extremely important to respond to the pandemic than nonstate actors. We find that perceptions of the role of state and nonstate actors are shaped by risk perception, political ideology and religion, gender, and race/ethnicity. We do not find evidence that direct impacts from the COVID‐19 pandemic consistently shape perceptions of the role of state and nonstate actors. 摘要: 本文中，我们分析了公众如何感知各级政府和非政府实体在响应新冠肺炎（COVID‐19）大流行一事中的重要性。通过分析COVID‐19案例，我们希望阐明不同模式，这些模式可能有助于理解公众如何感知更广范围的危机响应，包括飓风、龙卷风、地震、野火、以及其他灾害产生的影响。针对公众如何感知政府对危机的响应，我们对相关的公共政策文献作贡献，并对非国家行动者发挥的作用进行考量。基于一项包括德克萨斯州1200名登记选民的代表性调查，我们发现，个体更有可能将政府（而不是非国家行动者）视为极为重要的大流行响应者。我们发现，关于国家和非国家行动者发挥的作用的感知受风险感知、政治意识形态和宗教、性别、以及种族/族群性的影响。我们未发现证据证明COVID‐19大流行的直接影响会持续影响公众对国家和非国家行动者发挥的作用的感知。 RESUMEN: En este artículo, examinamos la percepción pública sobre la importancia de los diferentes niveles de gobierno y de las entidades no gubernamentales en la respuesta a la pandemia de COVID‐19. Al analizar el caso de COVID‐19, esperamos resaltar patrones que podrían ser útiles para comprender las percepciones públicas de la respuesta a una gama más amplia de crisis, incluidos los impactos de huracanes, tornados, terremotos, incendios forestales y otros peligros. Contribuimos a la literatura de políticas públicas sobre las percepciones públicas de la respuesta del gobierno a las crisis y la ampliamos para incluir la consideración del papel de los actores no estatales. Basándonos en una encuesta representativa de 1, 200 votantes registrados en Texas, encontramos que es más probable que las personas vean al gobierno como algo extremadamente importante para responder a la pandemia que los actores no estatales. Encontramos que las percepciones del papel de los actores estatales y no estatales están determinadas por la percepción del riesgo, la ideología política y la religión, el género y la raza / etnia. No encontramos evidencia de que los impactos directos de la pandemia de COVID‐19 moldeen consistentemente las percepciones del rol de los actores estatales y no estatales.